Deficiency and lack of vitamin d, polimorphism of the gene receptor of vitamin d and their influence on the intervertebral disc and back pain (literature review) - Povoroznyuk, Vladyslav; Dedukh, Ninel; Shinkarenko, Tatiana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Vitamin D has a pronounced metabolic effect on bone and cartilaginous tissue, which can have importance for the maintaining of a structural organization and metabolism of the intervertebral disc. Objective: based on the analysis of literature review, we assessed the impact of the vitamin D deficiency and itʼs lack, polymorphism of the vitamin D receptor on intervertebral disc in normal and with degenerative spine diseases, as well as the manifestation of lower back pain. The review presents the data about the features of the structural organization of intervertebral disc in the normal conditions and with degeneration, risk factors contributing to the degeneration and we evaluated the effect of vitamin D on the intervertebral disc structures. It was mentioned that in patients with degenerative spine diseases, as a rule, there is the deficiency of vitamin D, which affects the prognosis of the surgical treatment. The strategy for the prevention of these diseases can be an estimation of the level of this vitamin followed by its correction. Vitamin D deficiency in patients is associated with nonspecific pain syndrome in the lumbar spine. It was found that hypovitaminosis of vitamin D leads to a violation of bone metabolism and the function of muscle tissue, increased biosynthesis of proinflammatory cytokines, affects the modulating pain sensory neurons. The mechanisms leading to these violations require further studying. Of great importance is the study of polymorphism of the receptor gene vitamin D, which is related to degeneration of intervertebral disc, which is not the same for different populations of patients. Genetic studies of polymorphism of the receptor gene vitamin D gene have crucial for understanding the mechanisms of the degeneration of the intervertebral disc. Genetic information is important for determining of the risk of patients with degenerative spine diseases, in particular, symptomatic manifestations of intervertebral disc degeneration.